APPLICATION OF THE HOWARD’S MODEL ON CONSUMER BEHAVIOR IN BUYING INSURANCE POLICY - Paais, Martje; Souhoka, Semuel (International Journal of Engineering Technologies and Management Research, 2017)
This research intends to predict factors that drive consumer to buy insurance policy, based on consumer behavior model by Howard. In main variable used is buying decision. In addition, this study also includes information, brand image, confidence and attitude as the control variables. The analysis units are exclusive policy insured in Malang region. The data was collected using questionnaire. The t-test in simple regression models are used to test hypotheses. The research finds about: first, insignificant information to influence confidence and attitude, but statistically significant to influence brand image. Second, brand image are statistically significant to influence buying decision.